Seven stories up - Snyder, Laurel (Random House, 2014)
In 1987, while her mother sits in a Baltimore hotel at the deathbed of a grandmother twelve-year-old Annie never knew, Annie travels back fifty years and shares adventures with the lonely girl who will grow up to be her feisty grandmother.